(Sr0.6Bi0.305)2Bi2O7 as a new visible-light-responsive photocatalyst: An experimental and theoretical study. (October 2019) - Wang, Xinling; Liu, Lin; An, Huiting; Zhong, Yan; Wang, Dianhui; Tang, Chengying; Hu, Chaohao
Graphical abstract: The pyrochlore-type (Sr0.6 Bi0.305 )2 Bi2 O7 containing Bi 3+ and Bi 5+ mixed valent states was first investigated as a new photocatalytic material in this work and successfully synthesized by using a facile hydrothermal method. Our experimental measurements combining with the first-principles calculations show that (Sr0.6 Bi0.305 )2 Bi2 O7 is n-type semiconductor with a band gap of 1.25 eV. The as-prepared (Sr0.6 Bi0.305 )2 Bi2 O7 exhibits high photocatalytic efficiency and stability under visible light irradiation. The calculated electronic density of states indicates that Bi and O atoms close to the Sr vacancy probably possess higher activity and are helpful for its photocatalytic performance. Highlights: (Sr0.6 Bi0.305 )2 Bi2 O7 containing Bi 3+ and Bi 5+ mixed valent states was first investigated as a new photocatalytic material. The experimental measurements combining with the first-principles calculations show that (Sr0.6 Bi0.305 )2 Bi2 O7 is n-type semiconductor with a band gap of 1.25 eV. (Sr0.6 Bi0.305 )2 Bi2 O7 exhibits high photocatalytic efficiency and stability under visible light irradiation. Electronic structure calculations indicate that Bi and O atoms close to the Sr vacancy probably possess higher activity and are helpful for its photocatalytic performance. Abstract: The pyrochlore-type (Sr0.6 Bi0.305 )2 Bi2 O7 containing Bi 3+ and Bi 5+ mixed valent states was first investigated as a new photocatalytic material in this work and successfully synthesized by a facile hydrothermal method. The phase structure, morphology, microstructure, elemental composition, and optical properties of samples were characterized in details. The experimental measurements combining with the first-principles calculations show that (Sr0.6 Bi0.305 )2 Bi2 O7 is a n-type semiconductor with a band gap of 1.25 eV. The photocatalytic activity of (Sr0.6 Bi0.305 )2 Bi2 O7 was evaluated by the degradation of various organic dyes. Our results show that (Sr0.6 Bi0.305 )2 Bi2 O7 exhibits high photocatalytic efficiency and stability under visible light irradiation. The calculated electronic density of states indicates that Bi and O atoms close to the Sr vacancy probably possess higher activity and are helpful for its photocatalytic performance.